2017
DOI: 10.1111/cp.12067
|View full text |Cite
|
Sign up to set email alerts
|

From eating identity to authentic selfhood: Identity transformation in eating disorder sufferers following psychotherapy

Abstract: Background:The following article illustrates the development of the identity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Similar to OCD with repugnant obsessions, EDs are also frequently associated with guilt, shame and self‐disgust, except that the focus of such self‐loathing often revolves around one's bodily image (“I might be fat and unlovable”) rather than one's inner character (“I might be corrupt and immoral”). Moreover, a negative representation of the self is thought to also underlie ED symptomatology (Cooper, ; Cruzat‐Mandich, Díaz‐Castrillón, Escobar‐Koch, & Simpson, in press; Leung, Waller, & Thomas, ; Waller et al, ). As such, fear of self‐perceptions may apply to different manifestations of self, able to express itself either through a fear of a tainted inner (OCD) or bodily (ED) self.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to OCD with repugnant obsessions, EDs are also frequently associated with guilt, shame and self‐disgust, except that the focus of such self‐loathing often revolves around one's bodily image (“I might be fat and unlovable”) rather than one's inner character (“I might be corrupt and immoral”). Moreover, a negative representation of the self is thought to also underlie ED symptomatology (Cooper, ; Cruzat‐Mandich, Díaz‐Castrillón, Escobar‐Koch, & Simpson, in press; Leung, Waller, & Thomas, ; Waller et al, ). As such, fear of self‐perceptions may apply to different manifestations of self, able to express itself either through a fear of a tainted inner (OCD) or bodily (ED) self.…”
Section: Introductionmentioning
confidence: 99%
“…Our sample was somewhat heterogeneous in their recovery stage and age, especially in comparison to previous studies (Cruzat-Mandich, Díaz-Castrillón, Escobar-Koch, & Simpson, 2017;Ison & Kent, 2010;Petersson et al, 2017). Our sample was somewhat heterogeneous in their recovery stage and age, especially in comparison to previous studies (Cruzat-Mandich, Díaz-Castrillón, Escobar-Koch, & Simpson, 2017;Ison & Kent, 2010;Petersson et al, 2017).…”
Section: Limitationsmentioning
confidence: 46%
“…Despite the consistency of our findings with prior research, there are limitations. Our sample was somewhat heterogeneous in their recovery stage and age, especially in comparison to previous studies (Cruzat-Mandich, Díaz-Castrillón, Escobar-Koch, & Simpson, 2017;Ison & Kent, 2010;Petersson et al, 2017). Additionally, this sample had a high number of women with AN relative to the population of women with EDs, where AN is typically much less common (Stice, Marti, Shaw, & Jaconis, 2009).…”
Section: Limitationsmentioning
confidence: 88%
“…Our study also extends on previous evidence suggesting that impulse control, perfectionism, and DE are linked (Cruzat‐Mandich, Díaz‐Castrillón, Escobar‐Koch & Simpson, ). In this qualitative study, researchers identified that women with eating disorders tended to discuss how self‐control provided a sense of perfection, and that failure of achieve these standards of perfection caused intense distress (Cruzat‐Mandich et al ., ). Following from this evidence and our study, we believe that understanding how a specific form of perfectionism pressure (e.g., from fellow women) relates to impulsivity may lead to better clinical outcomes for reducing DE.…”
Section: Discussionmentioning
confidence: 99%